Evaluation of Intranasal Flap Perfusion by Intraoperative Indocyanine Green Fluorescence Angiography. Issue 6 (14th March 2018) - Geltzeiler, Mathew; Nakassa, Ana Carolina Igami; Turner, Meghan; Setty, Pradeep; Zenonos, George; Hebert, Andrea; Wang, Eric; Fernandez-Miranda, Juan; Snyderman, Carl; Gardner, Paul
Abstract: BACKGROUND: Vascularized intranasal flaps are the primary reconstructive option for endoscopic skull base defects. Flap vascularity may be compromised by injury to the pedicle or prior endonasal surgery. There is currently no validated technique for intraoperative evaluation of intranasal flap viability. OBJECTIVE: To evaluate the efficacy of indocyanine green (ICG) near-infrared angiography in predicting the viability of pedicled intranasal flaps during endoscopic skull base surgery through a pilot study. METHODS: ICG near-infrared fluorescence endoscopy was performed during endoscopic endonasal surgery for skull base tumors. Intraoperative and postoperative data were collected regarding enhancement of the flap body and pedicle. Fluorescence was rated qualitatively. Postoperatively, flap perfusion was evaluated via MRI-contrast enhancement in addition to clinical outcomes (cerebrospinal fluid leak and endoscopic flap appearance). RESULTS: Thirty-eight patients underwent ICG fluorescence angiography. Both the body and pedicle enhanced in 20 patients (53%), while the pedicle only enhanced for 12 patients (32%), the body only for 3 (8%), and neither for 3 (8%). When both the pedicle and body enhanced with ICG, the rate of postoperative MRI contrast enhancement was 100% and the rate of flap necrosis was 0%. The sensitivity and specificity of flap pedicle ICG enhancement for predicting postoperative flap MRI enhancement were 97% and 67%, respectively. Two of 3 patients without enhancement developed flap necrosis. CONCLUSION: ICG fluorescence angiography of intraoperative flap perfusion is feasible and correlates well with outcomes of postoperative MRI flap enhancement and flap necrosis. Additional study is needed to further refine the imaging technique and optimally characterize the clinical utility.